New Horizons in Mobile and Wireless Communications, Volume 1 : Radio Interfaces. - Prasad, Ramjee (Artech House, 2009)
Based on cutting-edge research projects in the field, this book (part of a comprehensive 4-volume series) provides the latest details and covers the most impactful aspects of mobile, wireless, and broadband communications development. These books present key systems and enabling technologies in a clear and accessible manner, offering you a detailed roadmap the future evolution of next generation communications. Other volumes cover Networks, Services and Applications; Reconfigurability; and Ad Hoc Networks.